2009
DOI: 10.1177/0218492309338120
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index-Monitored Anesthesia Technique for Transsternal Thymectomy

Abstract: To evaluate the role of bispectral index monitoring as an adjunct to balanced anesthesia in patients with myasthenia gravis undergoing transsternal thymectomy without the use of neuromuscular blocking agents, 10 patients were enrolled into this prospective observational study. After oral midazolam premedication, general anesthesia was induced with fentanyl, propofol, and sevoflurane. Tracheal intubation was performed without neuromuscular blocking agents. During maintenance, continuous monitoring of physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…MG patients are more sensitive than normal to the neuromuscular depressant effects of halothane and isoflurane [ 21 , 22 ]. Maddali et al [ 23 ] reported the safety use of sevoflurane and propofol when real-time monitoring the depth of anesthesia in a small cohort of patients undergoing transthymectomy. In contrast, Nitahara et al [ 24 ] have reported that sevoflurane inhibits neuromuscular transmission in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…MG patients are more sensitive than normal to the neuromuscular depressant effects of halothane and isoflurane [ 21 , 22 ]. Maddali et al [ 23 ] reported the safety use of sevoflurane and propofol when real-time monitoring the depth of anesthesia in a small cohort of patients undergoing transthymectomy. In contrast, Nitahara et al [ 24 ] have reported that sevoflurane inhibits neuromuscular transmission in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…We avoided succinylcholine in our patients to avoid prolonged blockade, as both of them were on cholinesterase inhibitor therapy [ 10 ]. We used lower doses of sevoflurane and propofol due to their desirable and proven pharmacological properties of rapid clearance, which were of benefit to these patients [ 11 ]. It is an established fact that reversal of neuromuscular blockade using Neostigmine is unpredictable in patients with MG, especially if they are taking anticholinesterase medication, which has been known to precipitate a cholinergic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…In general anesthesia, we preferred a neuromuscular-free approach and inhalational-intravenous combination (Sevoflurane -propofol) with maintenance on a combination of O 2 , N 2 O, Sevoflurane, and Propofol. Among inhalational and intravenous agents, sevoflurane and propofol are the preferred agents, respectively, due to their pharmacological properties [11].…”
Section: Discussionmentioning
confidence: 99%